OPTIMALISASI ASET WISATA SEJARAH MELALUI PENGEMBANGAN AKSESIBILITAS PARIWISATA DI DESA PARANGHARJO BANYUWANGI - Alifiara Arijanto, Tania; Rohmadian, Sindy; Zahro, Alfiatus; Rizqi Nur Hidayah, Laili; Ayu Fitria Sari, Putri; Amaliah, Rizky (LPPM Universitas Bina Bangsa, 2024)
Indonesia has great potential in the tourism sector by utilizing natural and cultural wealth. One of the tourism destinations in Indonesia, especially in Banyuwangi, has great potential in the historical tourism sector. This historical tourism is found in certain areas managed by the smallest governing body, namely the village. The purpose of this service is to optimize the accessibility of historical tourism assets in Parangharjo Village, such as the relics of the Puputan Bayu war; for example, the Sayu Wiwit Tomb. The service technique used is ABCD (Asset-Based Community Development) and data collection in the field is carried out through interview techniques by a number of parties. The results of the service focused on improving the accessibility of historical tourism in terms of infrastructure, namely by providing direction boards and building bridges to historical assets; as well as in terms of information, namely by making websites and information boards. The benefits of this service are preserving cultural and historical heritage and helping the mobility of the Parangharjo Village community in their daily lives